PENGARUH HARGA, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN BURGER KING JATIASIH - Noor Alimansyah; Devi Krisnawati; Fajar Cahyo Utomo (Jurnal Manajemen Bisnis Krisnadwipayana, 2022)
These study determine the influence of price, promotion and the quality of service on customer purchase decision at Burger King Jatiasih, Bekasi Indonesia. The data used are primary data by the answers of given questionnaires to customers of Burger King Jatiasih. These study using quantitative methodology. The analysis of the study used multiple linear regression analysis of three variables independent and one variable dependent. The results showed that the price has partially influenced the purchase decision, the promotion has partially influenced the purchase decision, the quality of service has partially influenced the purchase decision and the price, the promotion and the quality of service all have simultaneously influenced the purchase decision of Burger King Jatiasih’s customers.